(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
One of the functionaries who play a role in handling judicial mechanisms and organisms is an official called bailiff, formerly known as Deurwaarder. The bailiff is part of the executor of the District Court’s duties in examining and adjudicating civil cases. Has a role that is no less important than other officials in the Court, because its existence is needed from the start of the trial until the implementation of the Court’s decisions. This study aims to determine the effectiveness of the bailiff’s duties in the Pangkajene District Court and the factors that influence the effectiveness of the bailiff’s duties in the Pangkajene District Court. This study uses empirical research methods. Location the research was carried out in the city of Pangkep, especially in the court Pangkajene Country. Types and sources of data used are primary data and secondary data. Data collection technique, Library Research and Field Research (Field Research). Data analysis, namely data that has been obtained well primary data and secondary data will then be processed and analyzed to produce conclusions, then presented descriptive. The results of this study indicate that the effectiveness of the implementation of the bailiff’s duties in handling civil cases at the Pangkajene District Court has not been effective and found supporting and inhibiting factors in the effectiveness of the implementation of the Bailiffs at the Pangkajene District Court. The research recommendation is that the Bailiff at the Pangkajene District Court in handling civil cases must carry out procedures in accordance with the applicable rules. Abstrak: Salah satu fungsionaris yang ikut berperan dalam penanganan mekanisme serta organisme peradilan adalah pejabat yang disebut Juru Sita dahulu dinamakan Deurwaarder. Juru Sita merupakan bagian dari pelaksana tugas Pengadilan Negeri dalam memeriksa dan mengadili perkara perdata. Mempunyai peran yang tidak kalah penting dengan pejabat lain di Pengadilan, karena keberadaannya diperlukan sejak belum dimulainya persidangan hingga pelaksanaan putusan Pengadilan. Penelitian ini bertujuan untuk mengetahui efektifivitas pelaksanaan tugas juru sita di Pengadilan Negeri Pangkajene dan faktor-faktor yang mempengaruhi efektivitas pelaksanaan tugas juru sita di Pengadilan Negeri Pangkajene. Penelitian ini menggunakan metode penelitian empiris. Lokasi penelitian dilaksanakan di kota Pangkep khususnya di Pengadilan Negeri Pangkajene. Jenis dan sumber data yang digunakan adalah data primer dan data sekunder. Teknik pengumpulan data, Penelitian Pustaka (library Research) dan Penelitian Lapangan (Field Research). Analisis data yakni data-data yang telah diperoleh baik data primer maupun data sekunder kemudian akan diolah dan dianalisis untuk menghasilkan kesimpulan, kemudian disajikan secara deskriptif. Hasil penelitian ini menunjukkan bahwa efektivitas pelaksanaan tugas Juru Sita dalam menangani perkara perdata di Pengadilan Negeri Pangkajene belum efektif dan ditemukan faktor pendukung dan faktor penghambat dalam efektivitas pelaksanaan Juru Sita Pengadilan Negeri Pangkajene. Rekomendasi penelitian bahwa Juru Sita Pengadilan Negeri Pangkajene dalam menangani perkara perdata harus melakukan prosedur sesuai dengan aturan yang berlaku.